Advances on modeling in tissue engineering - Fernandes, Paulo R.; Bartolo, Paulo Jorge (Computational methods in applied sciences, 2011)
This book presents a collection of chapters describing the state of the art on computational modelling and fabrication in tissue engineering. Tissue Engineering is a multidisciplinary field involving scientists from different fields. The development of mathematical methods is quite relevant to understand cell biology and human tissues as well to model, design and fabricate optimized and smart scaffolds. The chapter authors are the distinguished keynote speakers at the first Eccomas thematic conference on Tissue Engineering where the emphasis was on mathematical and computational modeling for scaffold design and fabrication. This particular area of tissue engineering, whose goal is to obtain substitutes for hard tissues such as bone and cartilage, is growing in importance.